The Essence and Role of Electronic Money - Raiymbergenova, Kamshat; Zhatkanbayeva, Aizhan; Satbayeva, Aizhan; Gaitov, Alisher; Shansharbayeva, Botakoz (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of the study is to conduct legal analysis on the legal regulation problems concerning the concept of “electronic money” and the development of the modern monetary system of Kazakhstan based on the digitalisation of certain processes in the modern state. [Methodology/approach/design] Based on the legal and general scientific research methods, an analysis of the existing legal framework and other documents in the studied area was carried out. Also, a comparative-structural analysis of individual norms of legal acts of the Commonwealth of Independent States countries was made. [Findings] The issues of legal regulation and the incorporation of various concepts related to electronic money circulation into the laws of individual countries were examined based on the focus of the study. The idea of introducing a single digital electronic currency into Kazakhstan's national payment system, which would be backed by government finances and the obligations of the country's National Bank, was also substantiated. The arguments in support of this initiative by Kazakhstan's “main” bank and the country's government to launch a pilot process for the introduction of the digital tenge were formulated. This process will operate in circulation along with other cash and non-cash fiat currencies. In this regard, the chosen subject of the study is certainly promising for further scientific and theoretical deepening. This includes a further study of the prospects of digitalisation of the country's monetary system. Furthermore, a legal approach to the issue has revealed particular shortcomings in the enshrining of certain terms in Kazakhstan's legislation.